Memoria en conflicto : aproximaciones al concepto de memoria histórica en el proceso de construcción de paz en Colombia (2017)
In the midst of the peacebuilding process in Colombia, which is facing its initial stage of implementation, the concerns about what has been established between the Government and FARC-EP are becoming more critical and more visible. These concerns enquire about what is at stake in these agreements, what underlies its formulations and the possible implications this may have. With a particular emphasis on the fifth point of the agreement, "Regarding the Victims of the Conflict", this dissertation seeks to study the concept of Historical Memory proposed as an important part for an integral repair of victims in the so-called "Peace Building" process. The intention is to carefully analyze certain logics around the concepts of peace, conflict and violence that seem to be in the middle of the historical memory and its elaboration, and to also understand what this might entail. Ultimately, it is a matter of tracing and understanding what is politically...